Design of R.C. bored cast in-situ pile foundation under seismic liquefaction–A review of Indian codes - Chowdhury, Pronoy Roy (Journal of Structural Engineering, 2024)
During strong earthquakes submerged fine sandy layers may be subjected to liquefaction. BIS code IS-1893 recommends that the lateral resistance of liquefiable layers may be neglected. Use of deep foundation may be made to carry the load of the superstructure to non-liquefiable soil layers of superior bearing power. However as liquefiable layers offer no lateral resistance after liquefaction, the load carrying capacity of pile due to skin friction of liquefiable layers may be totally lost causing large settlement to the superstructure. If the depth of liquefiable layer is quiet large, due to loss of lateral resistance of liquefiable layer the unsupported length of pile may be of significant value, resulting in buckling of pile foundation under simultaneously acting axial and lateral seismic load. In this paper an attempt has been made to design an R.C.C bored cast-in-situ pile considering liquefaction of soil and buckling under lateral load as per existing provision of Indian standards, necessary comparison with unliquefied condition has also been attempted to indicate the extra sectional and reinforcement requirement for sustaining the superstructure against adverse settlement and tilting in the event of a strong motion earthquake inducing liquefaction.